How the removal of producer subsidies influences oil and gas extraction: A case study in the Gulf of Mexico. (1st January 2019) - Zhao, Xu; Luo, Dongkun; Lu, Kun; Wang, Xiaoyu; Dahl, Carol
Abstract: Since producer subsides can entail significant economic, fiscal, social and environmental costs, governments have been increasingly interested in removing them. Although many studies have been done on reducing consumer subsidies, subsidies to fossil fuel production are rarely discussed by scholars. This paper seeks to fill this void by developing an economic optimization model for oil and gas extraction to analyze the effects of producer subsidy removal. We forecast field-specific costs for exploration, development and production through constructing functions for the number of wells drilled and producing wells, production and economic limits. Various scenarios of phasing out producer subsidies in U.S. federal and state regulation on optimal production using field data from the Gulf of Mexico are simulated, including removing royalty relief, amortization of geological and geophysical costs, and percentage depletion. The results show that removal of producer subsidies reduces the optimal production rate and investors' net present value and increases government revenue, but the total effect is a cost of net social benefits. Changes in both the discount rate and oil price have positive effects on optimal production, but they exert opposite effects on producer benefits. Our research is helpful for policy-makers to regulate an efficient subsidy removal path. Highlights: An optimization model of oil and gas extraction with producer subsidy is established. Field specific costs are predicted through constructing the functions of wells drilled. We simulate various scenarios of producer subsidy removal. Producer subsidy removal reduces the optimal production and a cost of net social benefits. Both discount rates and oil price have positive effects on optimal production.